Danggui Buxue Tang, an ancient Chinese herbal decoction, protects β-amyloid-induced cell death in cultured cortical neurons - Gong, Guowei (BMC Complement Altern Med, 2019)
BACKGROUND: Danggui Buxue Tang (DBT) is a historical Chinese herbal decoction, and which has more than 800 years of applications. This herbal decoction solely contains two materials: Astragali Radix (AR) and Angelicae Sinensis Radix (ASR) at a weight ratio of 5:1. Clinically, DBT aims to improve anemia syndrome. In complementary and alternative medicine theory, the cause of neurodegenerative disease is proposed to be related with anemia. In line to this notion, low levels of hemoglobin and red blood cell have been reported in patients suffering from Alzheimer’s disease (AD), a chronic neurodegenerative disease caused by β-amyloid peptide (Aβ) accumulation. Therefore, we would like to probe the neuroprotective functions of this ancient herbal formula in vitro. METHOD: The neuroprotective effects of DBT in the Aβ-induced cell death were detected in cultured cortical neurons by multiple techniques, i.e. confocal and western blot. RESULTS: In the cultures, application of DBT reduced Aβ-induced apoptosis rate in a dose-dependent manner. In Aβ-treated cortical neurons, the expression ratio of Bcl2 to Bax was altered by DBT. In parallel, application of DBT markedly suppressed the Aβ-induced expressions of apoptotic markers, i.e. cleaved-caspase 3/9 and PARP. CONCLUSION: Taken these results, DBT shows promising protective effects against Aβ-induced stress or insult in cultured neurons.